Acid-resistant polyamine composite nanofiltration membrane and preparation method thereof

By using polyamine-containing dyes and triamyl chloride to polymerize interfacially, a polyamine composite nanofiltration membrane was formed, which solved the problem of poor separation performance of existing acid-resistant nanofiltration membranes in acidic environments, and achieved high permeability flux and good acid resistance.

CN119793247AInactive Publication Date: 2025-04-11BEIJING UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510012562.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing acid-resistant nanofiltration membranes have poor separation performance in acidic environments, especially the amide bonds of polyamide composite nanofiltration membranes are easily attacked by H+ and lead to structural damage, affecting the separation performance.

Method used

Dye molecules containing two or more amine groups are used as aqueous monomers and methylene chloride to polymerize interfacially to form a polyamine composite nanofiltration membrane. This method improves the separation performance of the film by forming a larger free volume and enhancing the hydrophilicity of the film surface.

Benefits of technology

The permeability flux and retention rate of the nanofiltration membrane are significantly improved, and especially in acidic environments, it shows good acid resistance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005228873900000011
    Figure HDA0005228873900000011
  • Figure HDA0005228873900000012
    Figure HDA0005228873900000012
  • Figure HDA0005228873900000013
    Figure HDA0005228873900000013
Patent Text Reader

Abstract

The invention discloses an acid-resistant polyamine composite nanofiltration membrane and a preparation method thereof, and belongs to the technical field of membrane separation. Adding a dye unit into deionized water to obtain a water phase solution, and adjusting the pH value to 7-13; adding cyanuric chloride into an organic solvent to obtain an organic phase solution; cleaning a base membrane, immersing the base membrane into the water-phase solution, then taking out the base membrane, and removing excessive water on the surface of the membrane; immersing into an organic phase solution for a period of time for interfacial polymerization; and placing the obtained composite membrane in a drying oven to obtain the dye / cyanuric chloride polyamine composite nanofiltration membrane. The dye is selected from acid fuchsin, basic fuchsin and the like. The obtained composite nanofiltration membrane is obviously improved in permeation flux, good in acid resistance and relatively high in rejection rate to negatively charged dyes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyamine composite nanofiltration membrane and a preparation method thereof, in particular to a high permeability flux acid-resistant polyamine composite nanofiltration membrane and a preparation method and application thereof, belonging to the technical field of membrane separation. Background Art

[0002] Industrial processes such as metal, mining, metallurgy, pharmaceuticals and papermaking produce a large amount of acidic wastewater. These wastewaters are complex in composition and contain high concentrations of acid, making it difficult and costly to harmlessly treat acidic wastewater. Nanofiltration membrane separation technology has the advantages of high separation efficiency, low energy consumption, low cost, simple operation, safety and stability, and has application prospects in treating acidic wastewater. Commonly used commercial nanofiltration membranes are mainly polyamide composite nanofiltration membranes, which have excellent desalination performance, but the amide bonds in them are easily affected by H in an acidic environment. + The membrane breaks due to the attack, which damages the structure of the selective layer of the composite membrane, thus affecting the separation performance and making it unsuitable for treating acidic wastewater.

[0003] At present, research on acid-resistant nanofiltration membranes is mostly focused on polysulfonamides, polyureas, triazine polyamines, etc. Among them, the carbon-nitrogen bonds formed by the alternating connection of nitrogen and carbon atoms in the triazine polyamine nanofiltration membrane replace the easily hydrolyzed amide bonds in the polyamide, and have good chemical stability and acid resistance. Triazine ring polyamine composite nanofiltration membranes are usually prepared by interfacial polymerization of amine monomers (such as polyethyleneimine) and cyanuric chloride. However, due to the long molecular chain and high functionality of polyethyleneimine, the permeation flux of the polyamine composite nanofiltration membrane obtained after interfacial polymerization with cyanuric chloride is low. Researchers have used a variety of methods to improve and enhance the separation performance of polyethyleneimine / melamine composite nanofiltration membranes. For example, Lee et al. (J. Membr. Sci., 2015, 478: 75-84) prepared polyethyleneimine / melamine composite nanofiltration membranes through interfacial polymerization of polyethyleneimine and cyanuric chloride. The pure water permeation flux is about 1.0 L·m -2 ·h -1 bar -1 When the concentrations of polyethyleneimine and cyanuric chloride were reduced, the pure water permeation flux of the composite nanofiltration membrane increased slightly to 2.7 L·m -2 ·h -1 bar -1, but the interception performance gradually deteriorated. Lasisi et al. (J. Membr. Sci., 2021, 640: 119833) used branched polyethyleneimine and 1,4-benzenecarboxylic acid as aqueous phase monomers and prepared polyamine composite nanofiltration membranes by interfacial polymerization with cyanuric chloride. The 1,4-benzenecarboxylic acid as a catalyst and comonomer can adjust the selection layer to form a rough surface structure, which can improve the permeation flux and interception performance of the composite nanofiltration membrane. The pure water permeation flux of the optimized branched polyethyleneimine / cyanuric chloride composite nanofiltration membrane is 12.8L·m -2 ·h -1 bar -1 Yu et al. (ACS Appl. Nano Mater. 2024, 7, 4388-4400) added piperazine, m-phenylenediamine, diethylenetriamine, and polyethyleneimine with a molecular weight of 600 to polyethyleneimine. These low molecular weight amine monomers have a fast diffusion rate and will form a loose primary layer through interfacial polymerization with cyanuric chloride, which will hinder the reaction between polyethyleneimine and cyanuric chloride to a certain extent, forming a thinner selective layer and improving the permeation flux of the polyamine composite nanofiltration membrane. Among them, the nanofiltration membrane with the addition of diethylenetriamine has the best performance, and the permeation flux of MgCl2 can be increased from 0.9L·m -2 ·h -1 bar -1 Increased to 3.4L·m -2 ·h -1 bar -1 Yu et al. (Sep. Purif. Technol., 2020, 250, 117245) prepared a Janus nanofiltration membrane with a loose selective layer and positively charged back and negatively charged front by reducing the concentration of cyanuric chloride. When the concentration of cyanuric chloride was 0.5 g / L, the pure water permeation flux of the polyethyleneimine / cyanuric chloride polyamine composite nanofiltration membrane was the highest, which was 10.4 L·m -2 ·h -1 bar -1 .

[0004] Patent CN107349804A discloses a method for preparing a high-flux acid-resistant nanofiltration membrane. The aqueous phase solution is prepared with aqueous phase monomers, amino graphene, and an acid-binding agent, and cyanuric chloride is used as an oil phase monomer. The high-flux acid-resistant nanofiltration membrane is prepared by interfacial polymerization, heat treatment, and other steps. The permeation flux of the nanofiltration membrane is low, about 5 L·m -2 ·h -1 bar -1However, graphene is prone to agglomeration, resulting in unstable separation performance of the membrane. Patent CN107930412B discloses an acid-resistant poly(amide-triazine-amine) nanofiltration composite membrane and its preparation method. The technology first prepares a poly(triazine)amine precursor, uses the precursor as a water phase monomer and a polyacyl chloride oil phase monomer for interfacial polymerization to obtain an acid-resistant poly(amide-triazine-amine) nanofiltration composite membrane. However, the pure water permeation flux of the nanofiltration membrane is low, which is 8.68L·m -2 ·h -1 bar -1 , and the precursor preparation process of this technology is complicated and difficult to operate.

[0005] Most dye organic compounds are conjugated structures formed by one or more benzene rings, with stable chemical properties and three-dimensional spatial structures. Fu et al. (Sep. Purif. Technol., 2025, 356, 129754) added Congo red dye to piperazine, used it as an aqueous phase monomer, and prepared a composite nanofiltration membrane by interfacial polymerization with trimesoyl chloride. Since the two amine groups at the para position of the benzene ring in Congo red react with the trimesoyl chloride interface to form a larger free volume, the permeation flux of the composite membrane is increased; moreover, the sulfonic acid group in Congo red enhances the hydrophilicity of the composite membrane surface, increases the negative charge of the membrane, and is beneficial to improve the retention performance of the composite membrane. However, the nanofiltration membrane prepared by interfacial polymerization of Congo red and trimesoyl chloride is still a polyamide membrane, and its separation performance in acidic solutions is still subject to great challenges. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides an acid-resistant polyamine composite nanofiltration membrane with high permeability flux and a preparation method and application thereof.

[0007] A method for preparing a high permeability flux acid-resistant polyamine composite nanofiltration membrane mainly comprises the following steps:

[0008] (1) Solution preparation: Add weighed dye into deionized water and stir thoroughly to obtain an aqueous phase solution with a mass concentration of 0.05-15%, and add an acid binding agent to adjust the pH value of the solution to 7-13; add cyanuric chloride into an organic solvent and stir thoroughly to obtain an organic phase solution with a mass concentration of 0.03-10.0%;

[0009] (2) Preparation of composite nanofiltration membrane: Cut the base membrane into appropriate size, place it in clean water for ultrasonic cleaning, immerse it in the aqueous phase solution prepared in step (1), take it out after 1 to 30 minutes, remove excess water on the membrane surface; immerse it in the organic phase solution prepared in step (1), perform interfacial polymerization at a temperature of 20 to 90°C, and take it out after 1 to 45 minutes.

[0010] (3) Post-treatment of the membrane: The composite membrane prepared in step (2) is placed in an oven and post-treated at 40 to 95° C. for 5 to 55 minutes to obtain a dye / melamine composite nanofiltration membrane.

[0011] Furthermore, the dye monomer used in the present invention is a dye molecule containing two or more amine groups, including but not limited to acid fuchsin and basic fuchsin;

[0012] Furthermore, the acid binding agent used in the present invention is a basic compound, which mainly functions to neutralize the H generated during the interfacial polymerization process. + , to promote the polymerization reaction, the acid-binding agent includes but is not limited to sodium hydroxide, potassium hydroxide, triethylamine, N,N-diisopropylethylamine;

[0013] Further, the base membrane used in the present invention is an ultrafiltration membrane with a molecular weight cutoff of 20 kDa to 100 kDa, including but not limited to polysulfone, polyethersulfone, polyetheretherketone, and polyvinylidene fluoride ultrafiltration membrane;

[0014] Furthermore, the organic solvent used in the present invention has a dielectric constant in the range of 1 to 3, including but not limited to n-heptane, n-hexane, cyclohexane, toluene, and N,N-dimethylpyrrolidone.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention uses dye molecules containing two or more amino groups as aqueous phase monomers, which have a three-dimensional spatial structure. Figure 1 As shown, the dye monomer and melamine chloride interfacially polymerize to form a polyamine separation layer with a large free volume, which is beneficial to improving the separation performance of the membrane. For example, the acid fuchsin / melamine chloride composite nanofiltration membrane prepared in Example 2 of the present invention has a retention rate of 95.8% for a 0.1 g / L aqueous solution of chrome blue black R, and a permeation flux of 36.6 L·m -2 ·h -1 bar -1 , attached Figure 2 The results show that the composite membrane also has good separation performance for other dyes and can be used for dye wastewater treatment. Secondly, the polyamine composite nanofiltration membrane prepared by the present invention has good acid resistance. After the polyamine composite nanofiltration membrane prepared in Example 2 was soaked in 15% mass concentration sulfuric acid for 30 days, the attached Figure 3 The scanning electron microscope image shows that the membrane surface structure is relatively complete; Figure 4 The results showed that the permeation flux of the polyamine composite nanofiltration membrane for 0.1g / L chrome blue black R aqueous solution was 37.2LMH / bar, and the rejection rate remained at about 95.4%. Figure 5As shown, the acid fuchsin / trimesoyl chloride polyamide composite nanofiltration membrane prepared in the comparative example, after being soaked in 15% (mass percentage concentration) sulfuric acid for 7 days, its permeation flux and interception rate for 0.1g / L chrome blue black R aqueous solution are significantly reduced, and the permeation flux and interception rate of the prepared acid fuchsin / melamine composite nanofiltration membrane are less reduced. The preparation method of the present invention is simple, and dye molecules are used as raw materials, which are cheap and easy to obtain, and the cost is low. The prepared dye / melamine composite nanofiltration membrane has significantly improved permeation flux, good acid resistance, and a high interception rate for negatively charged dyes. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 . Schematic diagram of the process of preparing dye / melamine composite nanofiltration membrane according to the present invention.

[0018] Figure 2 .The permeation flux and retention rate of the acid fuchsin / melamine composite nanofiltration membrane prepared in Example 2 of the present invention for nanofiltration separation of chrome blue black R, chrome black T, Congo red, methyl blue and Evans blue aqueous solutions with a mass concentration of 0.1 g / L.

[0019] Figure 3 . Surface scanning electron micrographs of the acid fuchsin / melamine composite nanofiltration membrane prepared in Example 2 of the present invention before and after being immersed in 15% mass concentration sulfuric acid for 30 days.

[0020] Figure 4 The retention rate and permeation flux changes of the acid fuchsin / melamine composite nanofiltration membrane prepared in Example 2 of the present invention for 0.1 g / L chrome blue black R aqueous solution were soaked in 15% mass concentration sulfuric acid for 0-30 days.

[0021] Figure 5 The acid fuchsin / trimethylenediamine composite nanofiltration membrane prepared in the comparative example of the present invention and the acid fuchsin / melamine composite nanofiltration membrane prepared in Example 2 were immersed in 15% mass concentration sulfuric acid for 0-7 days to measure (a) normalized permeation flux and (b) normalized retention rate of 0.1 g / L chrome blue black R aqueous solution. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the following implementation modes.

[0023] Comparative Example

[0024] The weighed acid fuchsin was added to deionized water, stirred evenly, and a water phase solution with a mass concentration of 0.5% was obtained. Sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 10; trimesoyl chloride was added to the n-hexane solution, stirred evenly, and an organic phase solution with a mass concentration of 0.2% was obtained. A polyetheretherketone ultrafiltration base membrane with a molecular weight cutoff of 50 kDa was immersed in the water phase solution, taken out after 10 minutes, and then immersed in the oil phase solution after removing excess water on the membrane surface, and an interfacial polymerization reaction was carried out at a temperature of 60°C. After 30 minutes, the composite membrane was placed in an oven and heat-treated at a temperature of 85°C for 15 minutes to obtain an acid fuchsin / trimesoyl chloride polyamide composite nanofiltration membrane.

[0025] The prepared acid fuchsin / trimesoyl chloride polyamide composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1 g / L chrome blue black R aqueous solution and the test pressure was 0.4 MPa. The results showed that the prepared acid fuchsin / trimesoyl chloride polyamide composite nanofiltration membrane had a retention rate of 91.4% for 0.1 g / L chrome blue black R aqueous solution and a permeation flux of 33.2 L·m -2 ·h -1 bar -1 .

[0026] Example 1

[0027] The weighed acid fuchsin was added to deionized water, stirred evenly, and an aqueous phase solution with a mass concentration of 0.05% was obtained. Sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 7; cyanuric chloride was added to n-hexane, stirred evenly, and an organic phase solution with a mass concentration of 0.03% was obtained. A polyetheretherketone ultrafiltration base membrane with a molecular weight cutoff of 20 kDa was immersed in the aqueous phase solution, taken out after 30 minutes, and then immersed in the oil phase solution after removing excess water on the membrane surface, and an interfacial polymerization reaction was carried out at a temperature of 90°C. After 1 minute, the composite membrane was placed in an oven and heat-treated at a temperature of 95°C for 5 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0028] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 92.5% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 38.8L·m -2 ·h -1 bar -1 .

[0029] Example 2

[0030] Acid fuchsin was added to deionized water and stirred to obtain a water phase solution with a mass concentration of 0.6%, and sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 10; cyanuric chloride was added to n-hexane and stirred to obtain an organic phase solution with a mass concentration of 0.4%. A polyetheretherketone ultrafiltration base membrane with a molecular weight cutoff of 50 kDa was immersed in the water phase solution, taken out after 12 minutes, and then immersed in the oil phase solution after removing excess water on the surface of the membrane, and interfacial polymerization reaction was carried out at a temperature of 60°C, and the composite membrane was taken out after 15 minutes, and the composite membrane was placed in an oven and heat treated at a temperature of 85°C for 8 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0031] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 95.8% for 0.1g / L chrome blue black R aqueous solution, and a permeation flux of 36.6L·m -2 ·h -1 bar -1 .

[0032] Example 3

[0033] The weighed acid fuchsin was added to deionized water and stirred to obtain a water phase solution with a mass concentration of 15.0%, and sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 13; cyanuric chloride was added to n-hexane and stirred to obtain an organic phase solution with a mass concentration of 10.0%. A polyetheretherketone ultrafiltration base membrane with a molecular weight cutoff of 100 kDa was immersed in the water phase solution, taken out after 1 minute, and then immersed in the oil phase solution after removing excess water on the membrane surface, and interfacial polymerization reaction was carried out at a temperature of 20°C, and the composite membrane was taken out after 45 minutes, and the composite membrane was placed in an oven and heat treated at a temperature of 40°C for 55 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0034] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 96.9% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 37.1L·m -2 ·h -1 bar -1 .

[0035] Example 4

[0036] The weighed basic fuchsin was added to deionized water, stirred evenly, and a water phase solution with a mass concentration of 0.5% was obtained. A triethylamine solution was added dropwise to adjust the pH value of the solution to 8.5; cyanuric chloride was added to N, N-dimethylpyrrolidone, stirred evenly, and an organic phase solution with a mass concentration of 0.3% was obtained. A polysulfone ultrafiltration base membrane with a molecular weight cutoff of 50 kDa was immersed in the water phase solution, taken out after 10 minutes, and then immersed in the oil phase solution after removing excess water on the surface of the membrane, and an interfacial polymerization reaction was carried out at a temperature of 50°C. After 25 minutes, the composite membrane was placed in an oven and heat-treated at a temperature of 60°C for 15 minutes to obtain a basic fuchsin / cyanuric chloride polyamine composite nanofiltration membrane.

[0037] The prepared basic fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared basic fuchsin / melamine composite nanofiltration membrane had a retention rate of 93.3% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 31.8L·m -2 ·h -1 bar -1 .

[0038] Example 5

[0039] The weighed basic fuchsin was added to deionized water and stirred to obtain a 1.0% aqueous solution, and N,N-diisopropylethylamine solution was added dropwise to adjust the pH value of the solution to 11; cyanuric chloride was added to n-heptane and stirred to obtain a 0.78% organic solution. A polyethersulfone ultrafiltration base membrane with a molecular weight cutoff of 50 kDa was immersed in the aqueous solution, taken out after 12 minutes, and then immersed in the oil phase solution after removing excess water from the membrane surface, and interfacial polymerization was carried out at 45°C. After 27 minutes, the composite membrane was placed in an oven and heat treated at 75°C for 12 minutes to obtain a basic fuchsin / cyanuric chloride polyamine composite nanofiltration membrane.

[0040] The prepared basic fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared basic fuchsin / melamine composite nanofiltration membrane had a retention rate of 94.8% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 29.0L·m -2 ·h -1 bar -1 .

[0041] Example 6

[0042] The weighed acid fuchsin was added to deionized water, stirred evenly, and a water phase solution with a mass concentration of 5.0% was obtained. Sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 12; cyanuric chloride was added to n-hexane, stirred evenly, and an organic phase solution with a mass concentration of 3.5% was obtained. A polyvinylidene fluoride ultrafiltration base membrane with a molecular weight cutoff of 80 kDa was immersed in the water phase solution, taken out after 7 minutes, and then immersed in the oil phase solution after removing excess water on the surface of the membrane, and an interfacial polymerization reaction was carried out at a temperature of 60°C. After 12 minutes, the composite membrane was placed in an oven and heat-treated at a temperature of 80°C for 10 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0043] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1 g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4 MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 95.1% for 0.1 g / L chrome blue black R aqueous solution, and a permeate flux of 35.5 L·m -2 ·h -1 bar -1 .

[0044] Example 7

[0045] The weighed basic fuchsin is added to deionized water, stirred evenly, and an aqueous phase solution with a mass concentration of 3.0% (w / v) is obtained. Potassium hydroxide solution is added dropwise to adjust the pH value of the solution to 9; cyanuric chloride is added to toluene, stirred evenly, and an organic phase solution with a mass concentration of 2.5% (w / v) is obtained. A polysulfone ultrafiltration base membrane with a molecular weight cutoff of 70 kDa is immersed in the aqueous phase solution, taken out after 6 minutes, and then immersed in the oil phase solution after removing excess water on the membrane surface, and an interfacial polymerization reaction is carried out at a temperature of 55°C, and the composite membrane is taken out after 22 minutes, and the composite membrane is placed in an oven and heat-treated at a temperature of 70°C for 16 minutes to obtain a basic fuchsin / cyanuric chloride polyamine composite nanofiltration membrane.

[0046] The prepared basic fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1 g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4 MPa. The results showed that the prepared basic fuchsin / melamine composite nanofiltration membrane had a retention rate of 91.6% for 0.1 g / L chrome blue black R aqueous solution, and a permeate flux of 32.1 L·m -2 ·h -1 bar -1 .

[0047] Example 8

[0048] The weighed acid fuchsin was added to deionized water and stirred to obtain a water phase solution with a mass concentration of 0.8%, and N,N-diisopropylethylamine solution was added dropwise to adjust the pH value of the solution to 11; cyanuric chloride was added to n-heptane and stirred to obtain an organic phase solution with a mass concentration of 0.6%. A polyetheretherketone ultrafiltration base membrane with a molecular weight cutoff of 60kDa was immersed in the water phase solution, taken out after 15 minutes, and then immersed in the oil phase solution after removing excess water on the membrane surface, and interfacial polymerization reaction was carried out at a temperature of 45°C. After 32 minutes, the composite membrane was placed in an oven and heat treated at a temperature of 55°C for 25 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0049] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 90.3% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 39.5L·m -2 ·h -1 bar -1 .

[0050] Example 9

[0051] The weighed acid fuchsin was added to deionized water, stirred evenly, and a water phase solution with a mass concentration of 3.6% was obtained. Sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 9.5; cyanuric chloride was added to n-heptane, stirred evenly, and an organic phase solution with a mass concentration of 4.35% was obtained. A polysulfone ultrafiltration base membrane with a molecular weight cutoff of 50 kDa was immersed in the water phase solution, taken out after 10 minutes, and then immersed in the oil phase solution after removing excess water on the surface of the membrane, and an interfacial polymerization reaction was carried out at a temperature of 50°C. After 28 minutes, the composite membrane was placed in an oven and heat-treated at a temperature of 45°C for 46 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0052] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 93.7% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 41.6L·m -2 ·h -1 bar -1 .

[0053] Example 10

[0054] The weighed acid fuchsin was added to deionized water, stirred evenly, and a water phase solution with a mass concentration of 1.6% was obtained. Sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8.5; cyanuric chloride was added to n-heptane, stirred evenly, and an organic phase solution with a mass concentration of 1.05% was obtained. A polysulfone ultrafiltration base membrane with a molecular weight cutoff of 50 kDa was immersed in the water phase solution, taken out after 8 minutes, and then immersed in the oil phase solution after removing excess water on the surface of the membrane, and an interfacial polymerization reaction was carried out at a temperature of 60°C. After 18 minutes, the composite membrane was placed in an oven and heat-treated at a temperature of 62°C for 25 minutes to obtain an acid fuchsin / cyanuric chloride polyamide composite nanofiltration membrane.

[0055] The prepared acid fuchsin / melamine composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The feed liquid was a 0.1g / L mass concentration of chrome blue black R aqueous solution, and the test pressure was 0.4MPa. The results showed that the prepared acid fuchsin / melamine composite nanofiltration membrane had a retention rate of 93.8% for 0.1g / L chrome blue black R aqueous solution, and a permeate flux of 38.6L·m -2 ·h -1 bar -1 .

Claims

1. A method for preparing a high permeability flux acid-resistant polyamine composite nanofiltration membrane, characterized in that: The following steps are involved: (1) Solution preparation: Add weighed dye units into deionized water and stir thoroughly to obtain an aqueous phase solution with a mass concentration of 0.05-15%, and add an acid binding agent to adjust the pH value of the solution to 7-13; add cyanuric chloride into an organic solvent and stir thoroughly to obtain an organic phase solution with a mass concentration of 0.03-10.0%; (2) Preparation of composite nanofiltration membrane: Cut the base membrane into appropriate size, place it in clean water for ultrasonic cleaning, immerse it in the aqueous phase solution prepared in step (1), take it out after 1 to 30 minutes, remove excess water on the membrane surface; immerse it in the organic phase solution prepared in step (1), perform interfacial polymerization at a temperature of 20 to 90°C, and take it out after 1 to 45 minutes. (3) Post-treatment of the membrane: The composite membrane prepared in step (2) is placed in an oven and post-treated at 40 to 95° C. for 5 to 55 minutes to obtain a dye / melamine composite nanofiltration membrane.

2. The method according to claim 1, characterized in that The dye monomer is a dye molecule containing two or more amine groups, including but not limited to acid fuchsin and basic fuchsin.

3. The method according to claim 1, characterized in that The acid-binding agent is an alkaline compound, including but not limited to sodium hydroxide, potassium hydroxide, triethylamine, and N,N-diisopropylethylamine.

4. The method according to claim 1, characterized in that The base membrane is an ultrafiltration membrane with a molecular weight cutoff of 20 kDa to 100 kDa, including but not limited to polysulfone, polyethersulfone, polyetheretherketone, and polyvinylidene fluoride ultrafiltration membranes.

5. The method according to claim 1, characterized in that The organic solvent has a dielectric constant in the range of 1 to 3, including but not limited to n-heptane, n-hexane, cyclohexane, toluene, and N,N-dimethylpyrrolidone.

6. A high permeability flux acid-resistant polyamine composite nanofiltration membrane prepared according to the method described in any one of claims 1 to 5.

7. Application of the high permeability flux acid-resistant polyamine composite nanofiltration membrane prepared by the method described in any one of claims 1 to 5, for filtering chrome blue black R, chrome black T, Congo red, methyl blue, Evans blue, especially chrome blue black R, chrome black T, Congo red, methyl blue, Evans blue under acidic conditions.

Citation Information

Patent Citations

  • Method for preparing composite charged mosaic membrane via interfacial polymerization

    CN101530748A

  • Method for preparing composite nanofiltration membrane by employing interfacial polymerization process

    CN103933881A

  • Preparation method of high-performance acid-resistant nanofiltration membrane

    CN116099393A